Effect of solid carburizing process using natural catalysts on the wear resistance ofAISI 1018 steel - S. Sujita; P. Pandiatmi; S. Suteja; I.P. Lokantara (Dinamika Teknik Mesin, 2026)
Low carbon steel AISI 1018 is extensively used in agricultural and mechanical components owing to its good formability and weld ability; however, its low surface hardness restricts its wear performance. Solid carburizing is a well-established surface hardening technique to address this limitation, while the utilization of natural catalysts derived from local biomass presents a sustainable and cost-effective alternative to conventional chemical activators. This study examines the effect of solid carburizing using natural catalysts broiler chicken bone powder, laying hen bone powder, and duck bone powder on the wear resistance of AISI 1018 steel. Carburizing treatments were performed using teak charcoal as the carbon source, mixed with the natural catalysts, at 900 Ã‚Â°C for 1, 1.5, 2, and 3 h, followed by rapid cooling to induce surface hardening. The treated specimens were evaluated through hardness measurements and dry sliding wear tests, complemented by microstructural analyses to assess surface morphology and effective case depth. The results reveal a pronounced increase in surface hardness and a significant improvement in wear resistance compared with untreated steel. These improvements are associated with enhanced carbon diffusion and the formation of a martensitic carburized layer after quenching. Overall, the findings demonstrate that solid carburizing assisted by natural catalysts is an effective approach to improving the wear resistance of AISI 1018 steel, offering a sustainable and economically viable surface modification route for low carbon steel employed in agricultural and engineering applications.